2015
DOI: 10.1021/bi501402k
|View full text |Cite
|
Sign up to set email alerts
|

Drug Modulation of Water–Heme Interactions in Low-Spin P450 Complexes of CYP2C9d and CYP125A1

Abstract: Azoles and pyridines are commonly incorporated into small molecule inhibitor scaffolds that target cytochromes P450 (CYPs) as a strategy to increase drug binding affinity, impart isoform-dependent selectivity, and improve metabolic stability. Optical absorbance spectra of the CYP–inhibitor complex are widely used to infer whether these inhibitors are ligated directly to the heme iron as catalytically inert, low-spin (type II) complexes. Here, we show that the low-spin complex between a drug-metabolizing CYP2C9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 41 publications
(128 reference statements)
7
31
0
Order By: Relevance
“…P450 inhibitors that exhibit type II optical spectra typically interact with the heme cofactor using the lone pair electrons of a nitrogen atom, with which they either directly coordinate to the heme iron or indirectly bind the heme iron by stabilising the axial heme water ligand. As such, fragment 1 a was predicted to interact with the heme iron using either the α‐amino group or indole nitrogen . Screening results from this initial set of fragment analogues indicated that the methyl ester of fragment 1 a was a key feature of the binding pharmacophore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P450 inhibitors that exhibit type II optical spectra typically interact with the heme cofactor using the lone pair electrons of a nitrogen atom, with which they either directly coordinate to the heme iron or indirectly bind the heme iron by stabilising the axial heme water ligand. As such, fragment 1 a was predicted to interact with the heme iron using either the α‐amino group or indole nitrogen . Screening results from this initial set of fragment analogues indicated that the methyl ester of fragment 1 a was a key feature of the binding pharmacophore.…”
Section: Resultsmentioning
confidence: 99%
“…As such, fragment 1a was predicted to interactw ith the heme iron using either the a-amino group or indole nitrogen. [36][37][38] Screening resultsf rom this initial set of fragment analogues indicatedt hat the methyl ester of fragment 1a was ak ey feature of the bindingp harmacophore. Replacement of the ester with ar ange of functional groups,i ncluding carboxylic acids, primary (thio)-amide, alcohol, amine or nitrile substituents disruptedh eme binding interactions (Dl max = 0nm).…”
Section: Substrate Deconstruction and Fragment Screeningmentioning
confidence: 99%
“…Low-spin heme is generally considered to arise from NOS OX with an axial water ligand on the heme and the high-spin heme from NOS with five-coordinate heme. However, local structural variations in the environment of the heme, e.g., in its hydrogen bonding network, within the active site can produce g-factor shifts of the magnitude seen here [36, 44]. The heme spectra in every sample can be fit with a mixture of the same five heme spectral components: two high-spin hemes and three low-spin hemes, Figure 2.…”
Section: Resultsmentioning
confidence: 98%
“…HYSCORE correlates ENDOR transitions of the same nucleus in different electron spin states and can resolve overlapping ENDOR transitions. The HYSCORE spectra were measured in the vicinity g z to determine hyperfine tensors that are not coaxial with the g-tensor [28, 35, 36]. …”
Section: Methodsmentioning
confidence: 99%
“…We suspected that the incorporation of heme into the CYP2C9 catalytic center may account for the decrease of the 1553 cm À1 signal in the 293T-Mig-2C9 cells. 43 The Raman band at 1442 cm À1 represents fatty acids, cholesterol and its esters, triglycerides (fatty acids) and CH 2 and CH 3 bending in lipids. It was reported that arachidonic acid (AA), a fatty acid that is usually esteried in membrane phospholipids in cells, was a substrate of CYP2C9.…”
Section: Sers Measurementmentioning
confidence: 99%